Engineering geological assessment of the permanent ship lock slope, the Three Gorges Project, China - Changyan, Chen; Sijing, Wang; Xiaoke, Shen (Journal of Nepal Geological Society, 2000)
The permanent ship lock slope of the Three Gorges Project was excavated through the hill of granite massif with the aspect of SE(106°). Some problems of engineering geology (such as statistical features of rock mass structure) were comprehensively studied based on field investigation and numerical analysis. The numerical modelling techniques including damage variable and finite element analysis were used for the detailed study of the effect of excavation and blasting on rock mass quality and slope stability. The analyses indicate that the rock mass is relatively intact and rock mass quality varies mainly from Class I to Class II. Consequently, the overall stability of slope can be ensured except for some minor local unstable blocks.